Critical Perspectives on Global Competition in Higher Education : New Directions for Higher Education, Number 168. - Portnoi, Laura M.; Bagley, Sylvia S.; Bagley, Sylvia S.; Portnoi,.; Bagley, Sylvia S.; Portnoi,. (Somerset : John Wiley & Sons, Incorporated, 2014)
This volume delivers a cutting-edge analysis on vernacular globalization, or how local forces mediate global trends. It delves into the vital facets of the quest for global competitiveness, including: Global university rankings World-class universities University mergers Quality assurance Cross-border higher education International education hubs. The authors situate their topics within current international scholarship and demonstrate the myriad avenues through which local actors in higher education may respond to global competition. They pose critical questions about the impact of global competition in an increasingly hierarchical higher education environment, interrogating the potential for social injustice that arises. By providing an alternative perspective to the descriptive, normative approach that dominates the scholarship on global competition in higher education, the chapters in this volume open a fresh and invaluable dialogue in this arena. This is the 168th volume of the Jossey-Bass quarterly report series New Directions for Higher Education. Addressed to presidents, vice presidents, deans, and other higher education decision makers on all kinds of campuses, it provides timely information and authoritative advice about major issues and administrative problems confronting every institution.
6 Cross-Border Higher Education: Global and Local Tensions Within Competition and Economic Development -- Types of Cross-Border Higher Education -- Students -- Faculty -- Curricular Programs -- Institutions -- Key Players and Motivations for Cross-Border Higher Education -- Home Institutions -- Importing Countries -- Exporting Countries -- Contested Campuses: Global Trends, Local Forces -- Institutional Effectiveness -- Community Engagement -- Conclusion -- References -- 7 International Education Hubs: Collaboration for Competitiveness and Sustainability -- A Working Definition of Education Hubs -- A Typology of Education Hubs: Student, Talent, and Knowledge/Innovation -- Highlights of Six International Education Hubs -- Education Hub Rationales in the Context of Globalization -- Conclusions: The Importance of Collaboration Among Policy Sectors -- References -- 8 A Critical Analysis of Global Competitionin Higher Education: Synthesizing Themes -- The Changing Higher Education Landscape -- The Drive Toward Global Competition -- Social Justice Considerations -- Tensions Between Global and Local Forces -- Concluding Remarks -- Reference -- INDEX -- Other Titles -- Order Form -- EULA.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Education, Higher; Competition, International; International education; Education and globalization; Electronic books